Synthesis and application of CuSO4-doped TiO2 for the visible light photocatalytic degradation of phenol - Santos, Basil James S.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Phenol is one of the most common persistent organic pollutants in aquaeous media. In this study, visible-light photocatalysis was used for the degradation of phenol using CuSO4-doped TiO2 prepared by a simple sol-gel process. The effects of different synthesis parameters, namely the amount of dopant, the amount of acid added during synthesis, and the calcination temperature, on phenol degradation were investigated. In addition, the effects of several operating parameters including pH, initial concentration, photocatalyst dosage, light wavelength, light intensity, and salinity on phenol degradation were also studied. Up to 100% phenol degradation and 50% COD removal was achieved in 1 h reaction time. The synthesized titania in this study can degrade phenol molecules 4 times higher with apparent rate constant of 10 times larger compared to Degussa P25. The Langmuir-Hinshelwood equation (R2 = 0.966) satisfactorily models the photocatalytic degradation of phenol under visible light. The calculated values for rate constant, k_LH and Langmuir adsorption constant, K_LH, are 0.726 min^-1 and 10.4 ppm^-1, respectively. This study has successfully demonstrated the effectiveness of CuSO4-doped TiO2 for the visible-light photocatalytic degradation of phenol.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman
Keywords: Phenols; Photocatalysis